2021
DOI: 10.1186/s13053-021-00189-8
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the phenotype of E318K (c.952G > A) MITF germline mutation carriers: case series and review of the literature

Abstract: Background The microphthalmia-associated transcription factor gene (MITF) belongs to the MYC supergene family and plays an important role in melanocytes’ homeostasis. Individuals harboring MITF germline pathogenic variants are at increased risk of developing cancer, most notably melanoma and renal cell carcinoma. Case presentation We describe a cohort of ten individuals who harbor the same MITF c.952G > A (p.Glu 318Lys), or p.E318K, germline pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“… 42 Moreover, a study from a Brazilian cohort from a hereditary cancer registry described a prevalence of 0.9% for this variant (10/1056 patients), with breast cancer being the most common cancer in probands and their relatives and no description of sarcomas. 43 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 42 Moreover, a study from a Brazilian cohort from a hereditary cancer registry described a prevalence of 0.9% for this variant (10/1056 patients), with breast cancer being the most common cancer in probands and their relatives and no description of sarcomas. 43 …”
Section: Discussionmentioning
confidence: 99%
“…42 Moreover, a study from a Brazilian cohort from a hereditary cancer registry described a prevalence of 0.9% for this variant (10/1056 patients), with breast cancer being the most common cancer in probands and their relatives and no description of sarcomas. 43 Recent studies have suggested that sarcoma susceptibility can result not only from monogenic high-risk variants but also from a combined effect of multiple less penetrant variants contributing to sarcoma risks through a polygenic risk model. 5 Specifically, polygenic effects and monoallelic germline variants in DNA damage response (DDR) genes were suggested to predispose patients to young-onset translocation-associated sarcoma subtypes, 5 as was later shown to be the case for FANCC variants in Ewing sarcomas.…”
Section: Discussionmentioning
confidence: 99%